A One Health perspective for integrated human and animal sanitation and nutrient recycling - Hung Nguyen-Viet; Phuc Pham Duc; Vi Nguyen; Tanner, M.; Odermatt, P.; Tu Vu-Van; Hoang Van Minh; Zurbrugg, C.; Schelling, E.; Zinsstag, Jakob (CAB International, 2015)
This chapter discusses a conceptual framework for integrated health and environmental assessment that combines health status, and the physical, socioeconomic and cultural environments in order to improve human health and minimize environmental impact. This concept's application in the management of human and animal excreta in Vietnam is then described.